Extraction of lineaments and faults using gravity second horizontal derivative data obtained using Fourier transform - Epuh, E.E.; Joshua, E.O. (Геофизический журнал, 2018)
Linear anomalies are important in the interpretation of gravity data because they indicate some important structural features. Gravity anomalies obtained from horizontal derivatives generally reflect lineaments and faults or compositional changes which can describe structural trends of a region. This study involves the delineation of the Gongola basin structural trend based on the convolution between the Fourier kernel obtained from the second horizontal derivative (SHD) of the truncated horizontal plate model (THPM) and the gravity anomaly. Линейные аномалии важны для интерпретации гравитационных данных, поскольку они являются индикаторами некоторых важных структурных особенностей. Крутые градиенты горизонтальных производных гравитационного поля обычно отражают линеаменты и разломы или изменения состава, позволяет описывать структурные тенденции региона. Это исследование направлено на выяснение структурного тренда бассейна Гонгола и основывается на конволюции ядра Фурье второй горизонтальной производной (ДГП) усеченной модели горизонтального слоя и аномалии гравитационного поля. Лінійні аномалії важливі для інтерпретації гравітаційних даних, оскільки вони є індикаторами деяких важливих структурних особливостей. Круті градієнти горизонтальних похідних гравітаційного поля зазвичай відображають лінеаменти і розломи або зміни складу, що дає змогу описувати структурні тенденції регіону. Це дослідження спрямоване на з’ясування структурного тренду басейну Гонгола і ґрунтується на конволюції ядра Фур’є другої горизонтальної похідної (ДГП) усіченої моделі горизонтального шару і аномалії гравітаційного поля.